Son preference, sex selection and the problem of missing women in India - Deepankar Basu (University of Massachusetts, Department of Economics, 2009)
This paper empirically tests for two competing explanations of the increasing sex ratio at birth (SRB) in India: hepatitis B and human intervention. Estimating a male- preferring stopping rule with data from three rounds of the National Family Health Survey in India (1992, 1998 and 2005), I find that the probability of a male birth varies significantly across birth parities. Using a novel proxy for hepatitis B in India - tribal status - I also find that hepatitis B has no impact on the probability of male birth. I conclude that human intervention explains the increasing SRB in India.
Keywords: J1; J7; 330